Review Paper on Electrical System for Size Based Box Sorting: DOI: 10.56815/IJEMS.V3.I2.2023/50-54 (International Journal of Engineering Management Science, 2023)
An important step forward in industrial automation has been made with the installation of an electrical system for size-based box sorting. This system uses sophisticated sensors, controllers, and actuators to optimize the sorting process. This project aims to decrease manual labour and errors while increasing overall efficiency. It addresses the critical need for improved supply chain management and logistics in many sectors. Modern technologies are integrated into the system, such as conveyor systems, box detecting sensors, and a size measurement system that uses laser or infrared sensors to measure dimensions precisely. The key components of the proposed system are a size measurement system that ensures precise dimension assessment, a conveyor system that facilitates smooth box transportation, and box detection sensors that identify the existence of boxes. The central processing unit is a micro-controller or PLC, which uses sensor data to make well-informed sorting decisions. Using pneumatic cylinders, solenoids, or servo motors, the sorting mechanism effectively directs boxes into specific chutes or conveyor lanes according to their size. Operators may easily monitor and control the sorting process with the help of the Human Machine Interface (HMI), and smooth information flow between system components is made possible by a strong communication system. Safety is the primary priority, and to that end, emergency stop mechanisms, safety sensors, and an extensive feedback system are all integrated to both prevent accidents and confirm the accuracy of the sorting. Thorough testing confirms the effectiveness of the system in a range of scenarios, taking into account variables like sorting accuracy, box size compatibility, and conveyor speed. The system's modular architecture facilitates maintenance and scalability, allowing it to be easily adjusted to meet the changing requirements of sectors that depend on effective box sorting. To sum up, this initiative promises increased accuracy and efficiency in supply chain management procedures, which is a significant advancement in logistics automation.
Keywords: Automation, Sorting, Electric system,Overall efficiency,Human machine interface